Inflasi, Suku Bunga, Debt to Ratio, Return on Equity : Manakah yang Lebih Berpengaruh terhadap Harga Saham? (Studi Empiris pada Perusahaan yang Terdaftar di JII Tahun 2013-2017) - Finoya Fitrahmisasty; Dina Patrisia (Universitas Negeri Padang, 2019)
Purpose - This study aims to analyze (1) the influence of fundamental variables (2) macroeconomic on stock prices in the companies registered in the Jakarta Islamic Index (JII) in 2013-2017.Methodology - This study considered the causative research. Types of data used is secondary data obtained from www.idx.co.id. The method of analysis used is multiple regression analysis. Finding - The results of this study concluded (1) Inflation has negative and no significant, (2) Interest rate has negative and no significant, (3) DR has positive and no significant (4) ROE has positive and significant effect on the stock price at companies registered in the Jakarta Islamic Index (JII) in 2013-2017. Keywords : Inflation, Interest Rate, DR, ROE, Price Shares, Jakarta Islamic Index